2001
DOI: 10.1139/g01-052
|View full text |Cite
|
Sign up to set email alerts
|

Soybean genomic survey: BAC-end sequences near RFLP and SSR markers

Abstract: We are building a framework physical infrastructure across the soybean genome by using SSR (simple sequence repeat) and RFLP (restriction fragment length polymorphism) markers to identify BACs (bacterial artificial chromosomes) from two soybean BAC libraries. The libraries were prepared from two genotypes, each digested with a different restriction enzyme. The BACs identified by each marker were grouped into contigs. We have obtained BAC- end sequence from BACs within each contig. The sequences were analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 31 publications
0
51
0
Order By: Relevance
“…The studies also suggested that the repetitive sequences were not evenly interspersed among single-copy sequences and clustering appeared to be similar to that found in wheat (Triticum aestivum) and rye (Secale cereale; Flavell and Smith, 1976;Smith and Flavell, 1977). Analysis of data generated from BAC end sequences suggests that although some regions are predominantly gene-rich or repetitive-rich, most loci contain a mixture of repetitive and genic sequences (Marek et al, 2001).…”
Section: Current Status Of Soybean Genomicsmentioning
confidence: 53%
See 1 more Smart Citation
“…The studies also suggested that the repetitive sequences were not evenly interspersed among single-copy sequences and clustering appeared to be similar to that found in wheat (Triticum aestivum) and rye (Secale cereale; Flavell and Smith, 1976;Smith and Flavell, 1977). Analysis of data generated from BAC end sequences suggests that although some regions are predominantly gene-rich or repetitive-rich, most loci contain a mixture of repetitive and genic sequences (Marek et al, 2001).…”
Section: Current Status Of Soybean Genomicsmentioning
confidence: 53%
“…The global gene space of soybean is not yet defined. However, gene-rich regions have been observed in soybean (Marek et al, 2001) using hypomethylated RFLPs as signatures of genic regions as compared to SSRs. Of more than 2,000 BAC-end sequences examined, RFLP-associated sequences had only one-half as many repetitive sequences and 50% more genic sequences compared with SSR-associated sequences.…”
Section: Current Status Of Soybean Genomicsmentioning
confidence: 99%
“…More than 750 SSR and RFLP markers were used to identify BAC clones in soybean. The markers anchor these BACs to the consensus molecular genetic map for soybean (Marek et al, 2001;Foster-Hartnett, et al, 2002). Almost 60% of the end sequences from BACs identified by both types of markers produce significant similarity in BLAST database searches.…”
Section: Building An Infrastructure Of Bac Contigs Anchored To the Gementioning
confidence: 99%
“…A marker-anchored Marek et al, 2001;Shultz et al, 2001) physical map of the soybean genome derived from large insert clones (Marek and Shoemaker, 1997;Danesh et al, 1998;Meksem et al, 2000) has been constructed and refined (C. Wu, personal communication). There are currently four routes available to access the data sets.…”
Section: Community Access To Project Resourcesmentioning
confidence: 99%
See 1 more Smart Citation